2023
DOI: 10.1186/s13071-023-05652-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of permethrin resistance in human head louse populations from northwest Iran: ex vivo and molecular monitoring of knockdown resistance alleles

Abstract: Background Head louse infestation is an important public health problem, and expanding resistance to permethrin is a major challenge to its control. The mapping and detection of pyrethroid resistance are essential to the development of appropriate treatments and ensure the effectiveness of current measures. The aim of this study was to present the phenotypic and genotypic basis of permethrin resistance and identify knockdown resistance (kdr) mutations in head louse populations in northwestern I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Recently, the identi cation of kdr amino acid substitutions, including M815I, T917I, and L920F, has been supplemented by the discovery of six new mutations within the extracellular loops of IIS1-2 (H813P) and IIS5 (I927F, L928A, R929V, L930M, and L923M), as well as the mutation F815I in head lice and the mutation N818D in body louse populations across the country. These alpha subunits have been demonstrated to be strongly linked with kdrresistance, and the presence of the F815I and N818D mutations has also been documented (Firooziyan et al, 2017;Ghavami et al, 2023). In the course of the present study, however, a total of four novel amino acid substitutions-namely, K794E, P813H, F815I, and N818Dwere identi ed in head lice for the very rst time.…”
Section: Introductionmentioning
confidence: 48%
See 3 more Smart Citations
“…Recently, the identi cation of kdr amino acid substitutions, including M815I, T917I, and L920F, has been supplemented by the discovery of six new mutations within the extracellular loops of IIS1-2 (H813P) and IIS5 (I927F, L928A, R929V, L930M, and L923M), as well as the mutation F815I in head lice and the mutation N818D in body louse populations across the country. These alpha subunits have been demonstrated to be strongly linked with kdrresistance, and the presence of the F815I and N818D mutations has also been documented (Firooziyan et al, 2017;Ghavami et al, 2023). In the course of the present study, however, a total of four novel amino acid substitutions-namely, K794E, P813H, F815I, and N818Dwere identi ed in head lice for the very rst time.…”
Section: Introductionmentioning
confidence: 48%
“…Examination of the kdr gene sequence in head lice within the purview of THUMS revealed the presence of haplotype I (M815I + T917I + L920F), which has previously been documented in Iran (Firooziyan et al, 2017;Ghahvechi Khaligh et al, 2021;Ghavami et al, 2023). A novel haplotype was also identi ed in the region, constituting the fth kdr haplotype in head lice.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Ebrahimi et al (2021) in Iran identified three kdr point mutations in amino acids D820E, L840F, and N874G, corresponding to the replacement of aspartic acid to glutamic acid, leucine to phenylalanine, and asparagine in the human head louse population, which L840F was identified as a new mutation [ 49 ]. Ghavami et al (2023) reported the presence of M815I, T917I and L920F mutations in 91.6, 4.2 and 4.2% of human head lice samples, respectively [ 50 ].…”
Section: Discussionmentioning
confidence: 99%